Awareness Mechanisms in Groupware Systems - Byrne, Peter (Trinity College Dublin. Department of Computer Science, 2004)
The main focus of this dissertation is to study the awareness mechanisms in groupware computing. The object of this study is to create a platform for testing awareness mechanisms in a general and empirical fashion. The platform will allow different awareness schemes to be enabled and disabled as required. The awareness mechanisms that will be supported in this project are the use of colour as a carrier of embodiment information, the use of radars and telepointers to present location awareness information in the workspace, the use of landmarks as a shorthand for navigation and reference in a shared workspace, and finally the effect of different levels of communications on the tasks. This study will conduct a pilot trial with groups of 2 to 4 users to test the effectiveness of the platform developed. Preliminary results from these trials will be summarised.
Keywords: Computer Science